The Oxford handbook of the history of communism - Smith, Stephen Anthony 1952- Hrsg (Oxford handbooks, 2014)
Towards a global history of communism / Stephen A. Smith -- Part 1. Ideology. Karl Marx and Friedrich Engels on communism / Paresh Chattopadhyay -- Lenin and Bolshevism / Lars T. Lih -- Stalin and Stalinism / Kevin McDermott -- Mao and Maoism / Timothy Cheek -- Part 2. Global moments. 1919 / Jean-François Fayet -- 1936 / Tim Rees -- 1956 / Sergey Radchenko -- 1968 / Maud Anne Bracke -- 1989 / Matthias Middell -- Part 3. Global communism. The Comintern / Alexander Vatlin and Stephen A. Smith -- Communism in Eastern Europe / Pavel Kolář -- Communism in China, 1900-2010 / Yang Kuisong and Stephen A. Smith -- Communism in South East Asia / Anna Belogurova -- Communism in Latin America / Mike Gonzalez -- Communism in the Islamic world / Anne Alexander -- Communism in Africa / Allison Drew -- Part 4. Communist polities and economies. Political and economic relations between communist states / Balázs Szalontai -- Averting Armageddon : the communist peace movement, 1948-1956 / Geoffrey Roberts -- The cult of personality and symbolic politics / Daniel Leese -- Communist revolution and political terror / Julia C. Strauss -- Popular opinion under communist regimes / Sheila Fitzpatrick -- Communism and economic modernization / Mark Harrison -- Collectivization and famine / Felix Wemheuer -- The politics of plenty : consumerism in communist societies / Paul Betts -- Part 5. Communism and social relations. The life of a communist militant / Marco Albeltaro -- Rural life / Jeremy Brown -- Workers under communism : romance and reality / Tuong Vu -- Communism and women / Donna Harsch -- Privilege and inequality in communist society / Donald Filtzer -- Nation-making and national conflict under communism / Adrienne Lynn Edgar -- Part 6. Communism and culture. Cultural revolution / Richard King -- Communism and the artistic intelligentsia / Mark Gamsa -- Popular culture / Dean Vuletic -- Religion under communism / Richard Madsen -- Sport under communism / Robert Edelman, Anke Hilbrenner and Susan Brownell